The Use of Ginkgo Biloba L. as a Neuroprotective Agent in the Alzheimer’s Disease - Nowak, Anna; Kojder, Klaudyna; Zielonka-Brzezicka, Joanna; Wróbel, Jacek; Bosiacki, Mateusz; Fabiańska, Marta; Wróbel, Mariola; Sołek-Pastuszka, Joanna; Klimowicz, Adam (Frontiers in Pharmacology, 2021)
Alzheimer's disease, a neurodegenerative disease, is one of the most common causes of dementia if elderly people worldwide. Alzheimer's disease leads to the alienation of individuals and their exclusion from social and professional life. It is characterized mainly by the degradation of memory and disorientation, which occurs as a result of the loss of neuronal structure and function in different brain areas. In recent years, more and more attention has been paid to use in the treatment of natural bioactive compounds that will be effective in neurodegenerative diseases, including Alzheimer's disease. G. biloba L. and its most frequently used standardized extract (EGb 761), have been used for many years in supportive therapy and in the prevention of cognitive disorders. The paper presents an overview of reports on the pathogenesis of Alzheimer's disease, as well as a summary of the properties of G. biloba extract and its effects on the possible pathogenesis of the disease. By exploring more about the pathogenesis of the disease and the benefits of G. biloba extract for patients with Alzheimer's disease, it will be possible to create an individualized therapeutic protocol to optimize the treatment.